Andalucía : a cultural history - Gill, John (John Joseph) (Landscapes of the imagination., 2009)
Preface and Acknowledgments Introduction: The Garden of Earthly Delights Part One: Iberia: From Prehistory to the Visigoths 1. Gardens of Stone 2. Tartessos 3. La Dama de Baza (Deities of Death) 4. Gadir/Cadiz 5. The Heavenly Cities of Baetica 6. Vandalucia Part Two: Al-Andalus: From Invasion to the Fall of Granada 7. Tariq's Rock 8. The Blackbird of Baghdad 9. Taming a Wilderness 10. The Library of Babel 11. Two Gentlemen of Cordoba Parr Three: Espana: From Reconquest to the Twenty-First Century 12. 1492 13. Taking the Garden Indoors 14. Nights in the Gardens of Spain 15.